1989
DOI: 10.1111/j.1365-2427.1989.tb01120.x
|View full text |Cite
|
Sign up to set email alerts
|

Floating meadow epiphyton: biological and chemical features of epiphytic material in an Amazon floodplain lake

Abstract: 1. Quantities and the chemical eomposition of epiphyton on the roots of floating aqualie macrophytes were measured in Lake Calado. an Amazon floodplain lake. Growth of epiphytic algae following physical disturbance and losses of epiphyton due to grazing and storms were investigated.2. Deposition of silt from invading river water deereased ehlorophyll and nutrient eontent (%C, %N, %P) of epiphyton during rising water. N:P ratios of epiphyton indicated that proximity to the river increased supplies of phosphorus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
7
0
2
Order By: Relevance
“…However, attached algae are often abundant on submersed surfaces of vascular plants. Studies in the Amazon floodplain have demonstrated that epiphytic microalgae in floating grass mats can have high productivity (Engle and Melack 1990;Doyle 1991).…”
Section: Discussionmentioning
confidence: 98%
“…However, attached algae are often abundant on submersed surfaces of vascular plants. Studies in the Amazon floodplain have demonstrated that epiphytic microalgae in floating grass mats can have high productivity (Engle and Melack 1990;Doyle 1991).…”
Section: Discussionmentioning
confidence: 98%
“…However, their light penetration data indicate an extinction coefficient of 2.4. Engle and Melack (1990) reported average daily irradiance of 20-25 Einst mm2 at a nearby location. Thus, the average column irradiance of 6.1 Einst m-2 d-l is strongly suggestive of light limitation for Jacaretinga.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to epiphyton productivity, epiphyton biomass has been widely studied ( e.g ., Engle & Melack , Mccormick et al . ), especially in temperate ecosystems ( e.g ., Turner et al .…”
mentioning
confidence: 99%